A stable compound of helium and sodium at high pressure - Dong, Xiao; Oganov, Artem R.; Goncharov, Alexander F.; Stavrou, Elissaios; Lobanov, Sergey; Saleh, Gabriele; Qian, Guang-Rui; Zhu, Qiang; Gatti, Carlo; Deringer, Volker L.; Dronskowski, Richard; Zhou, Xiang-Feng; et al. (Nature chemistry, 2017)
Helium is generally understood to be chemically inert and this is due to its extremely stable closed-shell electronic configuration, zero electron affinity and an unsurpassed ionization potential. It is not known to form thermodynamically stable compounds, except a few inclusion compounds. Here, using the ab initio evolutionary algorithm USPEX and subsequent high-pressure synthesis in a diamond anvil cell, we report the discovery of a thermodynamically stable compound of helium and sodium, Na 2 He, which has a fluorite-type structure and is stable at pressures >113 GPa. We show that the presence of He atoms causes strong electron localization and makes this material insulating. This phase is an electride, with electron pairs localized in interstices, forming eight-centre two-electron bonds within empty Na 8 cubes. We also predict the existence of Na 2 HeO with a similar structure at pressures above 15 GPa. Helium is generally recognized as being chemically inert. A thermodynamically stable compound of helium and sodium, Na 2 He, has been predicted computationally and then synthesized at high pressure. It exists as an electride, where strongly localized electrons serve as anions located at the centre of Na 8 cubes.